Genome-wide identification of GDPD gene family in foxtail millet (Setaria italica L.) and functional characterization of SiGDPD14 under low phosphorus stress - Meng, Chaomin; Guo, Haojie; Wang, Cheng; Yang, Furong; Du, Bing (Frontiers in Plant Science, 2025)
Glycerophosphodiester phosphodiesterase (GDPD) catalyzes the hydrolysis of glycerophosphodiesters into sn-glycerol-3-phosphate (G-3-P) and corresponding alcohols, which is integral to various physiological processes in plants. However, our comprehension of the GDPD gene family in foxtail millet (Setaria italica L.) remains limited and unclear. This study aimed to identify and predict the function of GDPD gene family members in foxtail millet through a comprehensive genome-wide analysis.14 SiGDPD genes were identified in the foxtail millet genome. Phylogenetic analysis categorized SiGDPD proteins into five groups. Promoter regions of SiGDPD genes contained multiple cis-acting elements related to light response, hormone regulation, and stress response. Phylogenetic and collinearity analyses demonstrated conservation of GDPD proteins among foxtail millet, sorghum, rice, and maize, with the SiGDPD gene family undergoing purifying selection during evolution.Tissue differential expression analysis revealed distinct expression patterns of SiGDPD genes across various tissues, showing spatiotemporal expression characteristics. Under low phosphorus stress, the expression levels of SiGDPD3 and SiGDPD14 significantly increased, while SiGDPD1, SiGDPD5, SiGDPD6, and SiGDPD11 showed significant decreases.To identify the function of SiGDPD14, an over-expressed transgenic Arabidopsis was generated. The results showed that transgenic Arabidopsis thaliana plants over-expressing SiGDPD14 exhibited enhanced tolerance to low phosphorus stress.Taken together, the results of this study provide valuable information for further studies on candidate SiGDPD genes involved in the phosphate deficiency response in foxtail millet.